Next-Generation Sequencing Approaches for the Identification of Pathognomonic Fusion Transcripts in Sarcomas: The Experience of the Italian ACC Sarcoma Working Group - Racanelli, Dominga; Brenca, Monica; Baldazzi, Davide; Goeman, Frauke; Casini, Beatrice; De Angelis, Biagio; Guercio, Marika; Milano, Giuseppe Maria; Tamborini, Elena; Busico, Adele; Dagrada, Gianpaolo; Garofalo, Cecilia; et al. (Frontiers in Oncology, 2020)
This work describes the set-up of a shared platform among the laboratories of the Alleanza Contro il Cancro (ACC) Italian Research Network for the identification of fusion transcripts in sarcomas by using Next Generation Sequencing (NGS). Different NGS approaches, including anchored multiplex PCR and hybrid capture-based panels, were employed to profile a large set of sarcomas of different histotypes. The analysis confirmed the reliability of NGS RNA-based approaches in detecting sarcoma-specific rearrangements. Overall, the anchored multiplex PCR assay proved to be a fast and easy-to-analyze approach for routine diagnostics laboratories.